Interactions between amyloid precursor protein-like (APPL) and MAGUK scaffolding proteins contribute to appetitive long-term memory in Drosophila melanogaster. (2nd January 2020) - Silva, Bryon; Niehage, Christian; Maglione, Marta; Hoflack, Bernard; Sigrist, Stephan J.; Wassmer, Thomas; Pavlowsky, Alice; Preat, Thomas
Abstract: Amyloid precursor protein (APP), the precursor of amyloid beta peptide, plays a central role in Alzheimer's disease (AD), a pathology characterized by memory decline and synaptic loss upon aging. Understanding the physiological role of APP is fundamental in deciphering the progression of AD, and several studies suggest a synaptic function via protein-protein interactions. Nevertheless, it remains unclear whether and how these interactions contribute to memory. In Drosophila, we previously showed that APP-like (APPL), the fly APP homolog, is required for aversive associative memory in the olfactory memory center, the mushroom body (MB). In the present study, we show that APPL is required for appetitive long-term memory (LTM), another form of associative memory, in a specific neuronal subpopulation of the MB, the α′/β′ Kenyon cells. Using a biochemical approach, we identify the synaptic MAGUK (membrane-associated guanylate kinase) proteins X11, CASK, Dlgh2 and Dlgh4 as interactants of the APP intracellular domain (AICD). Next, we show that the Drosophila homologs CASK and Dlg are also required for appetitive LTM in the α′/β′ neurons. Finally, using a double RNAi approach, we demonstrate that genetic interactions between APPL and CASK, as well as between APPL and Dlg, are critical for appetitive LTM. In summary, our results suggest that APPL contributes to associative long-term memory through its interactions with the main synaptic scaffolding proteins CASK and Dlg. This function should be conserved across species.